On-ground and on-orbit time calibrations of GECAM. Issue 1 (14th January 2022) - Xiao, S; Liu, Y Q; Peng, W X; An, Z H; Xiong, S L; Tuo, Y L; Gong, K; Zhang, P; Zhang, K; Zheng, S J; Li, C Y; Gao, M; et al.
ABSTRACT: High time resolution and accuracy are of critical importance in the studies of timing analysis and time delay localization of gamma-ray bursts (GRBs), soft gamma-ray repeaters (SGRs) and pulsars. The Gravitational wave high-energy Electromagnetic Counterpart All-sky Monitor (GECAM) consisting of two micro-satellites, GECAM-A and GECAM-B, launched on 2020 December 10, is aimed at monitoring and locating X-ray and GRBs all over the sky. To achieve its scientific goals, GECAM is designed to have the highest time resolution (0.1 μ s ) among all GRB detectors ever flown. Here, we make a comprehensive time calibration campaign including both on-ground and on-orbit tests to derive not only the relative time accuracy of GECAM satellites and detectors, but also the absolute time accuracy of GECAM-B. Using the on-ground calibration with a ^22Na radioactive source, we find that the relative time accuracy between GECAM-A and GECAM-B is about 0.15 μ s (1 σ ). To measure the relative time accuracy between all detectors of a single GECAM satellite, cosmic-ray events detected on orbit are utilized since they could produce many secondary particles simultaneously record by multiple detectors. We find that the relative time accuracy among all detectors onboard GECAM-B is about 0.12 μ s (1 σ ). Finally, we use the novel Li-CCF method to perform the absolute time calibration with Crab pulsar and SGR J1935+2154, both of which were jointly observed by GECAM-B and Fermi /GBM, and obtain that the time difference between GECAM-B and Fermi /GBM is 3.06 ± 6.04 μ s (1 σ ).